Complex Metabolomic Changes in a Combined Defect of Glycosylation and Oxidative Phosphorylation in a Patient with Pathogenic Variants in PGM1 and NDUFA13 - Silvia Radenkovic; Isabelle Adant; Matthew J. Bird; Johannes V. Swinnen; David Cassiman; Tamas Kozicz; Sarah C. Gruenert; Bart Ghesquière; Eva Morava (Cells)
Inherited metabolic disorders (IMDs) are genetic disorders that occur in as many as 1:2500 births worldwide. Nevertheless, they are quite rare individually and even more rare is the co-occurrence of two IMDs in one individual. To better understand the metabolic cross-talk between glycosylation changes and deficient energy metabolism, and its potential effect on outcomes, we evaluated patient fibroblasts with likely pathogenic variants in PGM1 and pathogenic variants in NDUFA13 derived from a patient who passed away at 16 years of age. The patient presented with characteristic of PGM1-CDG including bifid uvula, muscle involvement, abnormal glycosylation in blood, and elevated liver transaminases. In addition, hearing loss, seizures, elevated plasma and CSF lactate and a Leigh-like MRI brain pattern were present, which are commonly associated with Leigh syndrome. PGM1-CDG has been reported in about 70 individuals, while NDUFA13 deficiency has so far only been reported in 13 patients. As abundant energy is essential for glycosylation, and both PGM1 and NDUFA13 are linked to energy metabolism, we sought to better understand the underlying biochemical cause of the patient’s clinical presentation. To do so, we performed extensive investigations including tracer metabolomics, lipidomics and enzymatic studies on the patient’s fibroblasts. We found a profound depletion of UDP-hexoses, consistent with PGM1-CDG. Complex I enzyme activity and mitochondrial function were also impaired, corroborating complex I deficiency and Leigh syndrome. Further, lipidomics analysis showed similarities with both PGM1-CDG and OXPHOS-deficient patients. Based on our results, the patient was diagnosed with both PGM1-CDG and Leigh syndrome. In summary, we present the first case of combined CDG and Leigh syndrome, caused by (likely) pathogenic variants in PGM1 and NDUFA13, and underline the importance of considering the synergistic effects of multiple disease-causing variants in patients with complex clinical presentation, leading to the patient’s early demise.